Pengembangan Formula Berbasis Bahan Pangan Lokal sebagai Alternatif PMT Balita Stunting (Kacang Merah dan Umbi Talas) - Angelina Agustin Ika Nur 'Aini; Fila Rachmad Ramadhan; Farida Nur Isnaeni (INSOLOGI: Jurnal Sains dan Teknologi, 2026)
The prevalence of malnutrition in Central Java in 2022 was 5.3%, which is considered serious. One effort to address malnutrition is the provision of calorie-dense supplementary foods based on local foods such as baked brownies. The purpose of this study was to develop a special diet formula based on red beans and taro tubers. This study was an experimental study with a completely randomized design (CRD) with three formulas (F375, F629, and F814). The results showed that the water content test of the baked brownie formula met the Indonesian National Standard (SNI) (<40%). The color test of each formula for indicator "l" tended to be bright, indicator "a" tended to be red, and for indicator "b" tended to be yellow. Organoleptic analysis was performed using Kruskal Wallis with a p-value of 0.497 for color; p-value of 0.271 for aroma; p-value of 0.619 for taste; p-value of 0.174 for texture; and p-value of 0.485 for overall). There was no difference in organoleptic terms, but there was a tendency for preference. The development of the baked brownie formula that was most preferred by the panelists was F629 with a ratio of 35 grams of red beans and 70 grams of taro tubers